Extracting Semantic Frames from Specialized Corpora for Lexicographic Purposes - Sánchez Cárdenas, Beatriz (Círculo de Lingüística Aplicada a la Comunicación, 2024)
This paper focuses on Frame-based Terminology (FBT), a theoretical framework based on cognitive premises that underpin the representation of specialized objects and events. It demonstrates that specialized semantic frames can be inferred from lexical schemas and semantic annotation. This research used corpus techniques to collect data for the representation of multilingual semantic frames. The research focuses on deforestation within the domain of Environmental Science. The methodology involves the encapsulation of corpus queries and semantic annotation to guide the creation of specialized frames associated with the deforestation event. Although the creation of frame-based terminological resources can be time-consuming, our results show that it is facilitated by the use, of e-tools that extract the arguments of specialized predicates, which are often immersed in complex syntactic constructions.